Roald Dahl's Revolting rhymes - Dahl, Roald; Blake, Quentin (New York : Alfred A. Knopf, 2002)
Humorous retellings in verse of six well-known fairy tales featuring surprise endings in place of the traditional happily-ever-after.
Originally published: Great Britain : Jonathan Cape, 1982.
HG 09/02
0710
Keywords: Children's poetry, English; English poetry -- Juvenile literature; Humorous poetry -- Juvenile literature; Narrative poetry -- Juvenile literature; Fairy tales